Corporate Governance and Beta of Listed Companies at BM&FBOVESPA - DOI: http://dx.doi.org/10.16930/2237-7662/rccc.v14n43p51-62 - Cazzari, Roberto Bomgiovani (2015)
This paper aimed at studying the relationship between the level of corporate governance and the betas of the companies. If all investors are rational, as foreseen in the CAPM, they are already working with minimum variance portfolios, according to Markowitz (1952). Thus, the only risk that everyone would be subjected to was the systemic risk. Additionally, these same investors would keep the same market portfolio for all risky assets. Therefore, in this view, an idiosyncratic risk as the risk of poor governance should already have been diversified in the previous step and should not be directly related to the beta of a given company. In this view, the beta would represent only risks linked to the systemic aspect. However, Parigi, Pelizzon and von Thadden (2013) proposed a model that includes corporate governance to the CAPM. Unlike seen by the classical theory of the CAPM, these authors developed a model that predicts that the quality of corporate governance is positively correlated with beta and idiosyncratic volatility, but negatively correlated with the return on assets. To test which theory has better explanatory power for the Brazilian scenario, we tested the hypothesis of independence between the beta and the quality of corporate governance of companies listed at BM&FBOVESPA. The findings of this paper have not shown that the quality of corporate governance is positively related with the beta, but that they are independent. This seems to be a strong indication that the beta in the Brazilian scenario does not reflect an idiosyncratic risk as the risk of bad governance, but a systemic risk which relates better to the classical theory of CAPM.